Molecular Landscape of Seed Senescence: Dissecting Micro and Macro Molecular Alterations and their Amelioration Strategies - SS BHARATH; V K DESHPANDE; MADHU CHALAGERI; SEEMA S DODDAMANI (Seed Research, 2025)
Seed senescence, the final stage of seed development, involves intricate molecular processes that transition from nutrient assimilation to nutrient remobilization. As seeds age, macromolecules such as nucleic acids, proteins and lipids undergo catabolism. These nutrients are then exported to other developing plant parts, including new buds, young leaves, flowers, or seeds, ultimately enhancing reproductive success. Researchers have made significant strides in understanding the genetic and molecular mechanisms underlying seed senescence, aided by the identification of senescence-associated genes (SAGs) and functional assessments in model plants like Arabidopsis thaliana. This review delves into the molecular mechanisms underlying seed aging, highlighting the roles of gene expression changes, DNA methylation and chromatin modifications. Reactive oxygen species (ROS) and oxidative stress are identified as key factors contributing to cellular damage during seed aging. The regulation of seed senescence involves complex networks, including chromatin, transcription and post-translational processes. Strategies to manipulate seed senescence aim for improved crop yield, quality and performance. The changes that are associated with seed aging & seed ageing/senescence has been reviewed at molecular levels.